268 INFLUENZA SEASON TRIGGERS PNEUMOCOCCAL VACCINATION. (1st January 2006) - Goebel, L.; Mufson, M.
Abstract : Purpose: The CDC recommends that clinicians administer influenza and pneumococcal vaccines at the same time as one approach to increase the frequency of pneumococcal vaccination. We investigated the rates with which these vaccines are administered in our practice and the frequency with which they are administered together to vaccine-eligible seniors. Methods: We reviewed the billing records of patients 65 years and older from 1999 through 2005 for administration of pneumococcal and influenza vaccines in our university internal medicine ambulatory care practice. We calculated rates of administration of pneumococcal and influenza vaccines given alone and together. Results: Nine hundred sixty-nine doses of pneumococcal vaccine were administered, and of these, 796 (82%) were administered during the fall and winter months. Three hundred fifty-seven (38%) pneumococcal vaccinees received it together with influenza vaccine. During 2001 and 2005, when influenza vaccine supply was limited, the rate of pneumococcal vaccine administered together with influenza vaccine declined sharply (from 2.3 in 2000 to 1.4 in 2001 and from 1.3 in 2004 to 0.4 in 2005). Nonetheless, the rate of pneumococcal vaccination remained relatively stable due to an increase in the rate of pneumococcal vaccine administered alone (from 2.1 in 2000 to 3.2 in 2001 and from 1.9 in 2004 to 3.1 in 2005). Conclusions: Although pneumococcal vaccine can be administered at any time of year, in our practice most pneumococcal vaccines were administered in the fall and winter months and about one-third of these were given together with influenza vaccine. In years when the influenza vaccine supply was limited, physicians in our practice continued to vaccinate with pneumococcal vaccine alone so that the total rate of administration of pneumococcal vaccine remained stable. These findings suggest that the imminent influenza season, rather than the availability of influenza vaccine, provides the trigger for physicians to prescribe pneumococcal vaccine. Physicians should be reminded that pneumococcal vaccine can be administered at any time of year.